Traumatic intralenticular abscess—What is so different? - Balamurugan, S; Gurnani, Bharat; Kaur, Kirandeep; Gireesh, Prasanth; Narayana, Shivanand (Indian Journal of Radiology and Imaging, 2020)
Intralenticular abscess is a very rare entity that occurs after trauma, cataract surgeries, or as metastatic infection. It is important to pinpoint this sequestrated infection and to evacuate the abscess surgically to prevent chronic endophthalmitis. In this report, we describe a case of posttraumatic lenticular abscess highlighting the characteristic clinical features and their management. Additionally, here we report the first time use of Anterior Segment Optical Coherence Tomography as a diagnostic tool in delineating lens abscess from traumatic cataract which further guide the management and prognosis of the case.Traumatic intralenticular abscess (TILA)—What is so different?
Keywords: Anterior segment optical coherence tomography; B scan; intralenticular abscess; moraxella; trauma